SEaM mobile card game and animated video for increasing knowledge and attitudes of early marriage prevention - Susmita Sari, Apriani; Lia Basuni, Hikmah; Fitria Aprianti, Nurannisa (International Journal of Public Health Science (IJPHS), 2025)
An international problem that might jeopardize the lives, futures, and well-being of adolescents is early marriage. A couple who marries before the age of eighteen is considered an early marriage. Knowledge and attitudes towards early marriage are among the variables that can impact its incidence. This study aimed to determine the effect of using the SEaM Mobile Card Game and animated videos on increasing the knowledge and attitudes of adolescents about early marriage prevention. The research design is a quasi-experiment with a non-equivalent approach (pre-test and post-test) control group design. The sample amounted to 148 respondents. The instruments used in this study were knowledge questionnaires on early marriage prevention, attitude questionnaires on early marriage prevention and usefulness, ease of use, ease of learning, and satisfaction (USE) questionnaires. The research data were analyzed using Wilcoxon and Mann Whitney with a significance level of p<0.05. The results of this study were that there was a significant difference in adolescent knowledge about early marriage prevention in the SEaM Mobile Card Game group and animated videos after education (p=0.013) and there was a significant difference in adolescents' attitudes toward early marriage prevention in the SEaM Mobile Card Game group and animated videos after education (p=0.000).